Analyzing the Impact of Internal Factors on MSME Environmental Management for Sustainable Development in Aceh Tamiang Regency - Rita Syntia; Muhammad Isra (School of Postgraduate Studies, Diponegoro Univer, 2025)
The growth of Micro, Small and Medium Enterprises (MSMEs) has not been fully supported by the implementation of environmentally sustainable management strategies. This study aims to identify internal factors influencing environmentally friendly waste management among MSMEs and to measure their contribution to sustainable development in Aceh Tamiang Regency. The main focus is to assess how organizational structure, resource management, and environmental awareness within MSMEs affect sustainable empowerment, particularly in sectors that generate waste. The study population consists of 965 waste-producing MSMEs, with a sample of 300 respondents selected using purposive sampling to match the research criteria. Data was collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM) with the assistance of AMOS software. SEM was chosen for its ability to test complex relationships among variables simultaneously and provide strong validity for the theoretical model. The findings show that internal company factors such as demographics, human resources, corporate culture, management practices, marketing, innovation capability, and employee awareness significantly influence MSME empowerment in adopting environmentally friendly practices. Furthermore, this empowerment contributes positively to sustainable development by reducing environmental impacts and improving economic efficiency. These findings are important for policymakers in Aceh Tamiang in designing sustainability-based strategies and policies for the development of local MSMEs.